Synergistic effect induced ultrafine SnO2/graphene nanocomposite as an advanced lithium/sodium-ion batteries anode. Issue 20 (10th May 2017) - Chen, Weihua; Song, Keming; Mi, Liwei; Feng, Xiangming; Zhang, Jianmin; Cui, Shizhong; Liu, Chuntai
Abstract : A synergistic effect induced ultrafine-SnO2 /graphene nanocomposite is synthesized via a simple method as an advanced lithium/sodium-ion batteries anode material. Abstract : SnO2 /graphene materials have received extensive attention in broad applications owning to their excellent performances. However, multi-step and harsh synthetic methods with high temperatures and high pressures are major obstacles that need to be overcome. Herein a simple, low-cost, and scalable approach is proposed to construct ultrafine SnO2 /graphene nanomaterials effectively under constant pressure and at the low temperature of 80 °C for 4 h, in which ultrafine SnO2 nanoparticles grow on graphene sheets uniformly and firmly via Sn–O–C bonding. This result depends on the synergetic effect of two reactions, the reduction of graphene oxide and formation of SnO2 nanoparticles, which are achieved successfully. More importantly, the constructed SnO2 /graphene material exhibits excellent electrochemical properties in both lithium-ion batteries and sodium-ion batteries. As an anode material for lithium-ion batteries, it displays a high reversible capacity (1420 mA h g −1 at 0.1 A g −1 after 90 cycles) and good cycling life (97% at 1 A g −1 after 230 cycles), whereas in sodium-ion batteries, it maintains a capacity of 1280 mA h g −1 at 0.05 A g −1 and 650 mA h g −1 at 0.2 A g −1 after 90 cycles. The proposed synthetic methodology paves the way for the effective and large scale preparation of graphene-based composites for broad applications such as energy storage, optoelectronic devices, and catalysis.